A web based application on student outcome management system - Prema Sindhuri, B; Harika, S; Soumigna Sai, T (International Journal of Engineering and Technology, 2018)
The main purpose of this specification is to provide a clear view of the result analysis on student performance and as well as faculty and also for the parents. This project aims at developing an a web based application on student result analysis. The faculty assign student overall marks on this particular web application and this overall outcome will be send to all the parents at a time. This system is ideal for adult schools, educational institutions and other training programs. The Scope of the software product developed involves services to the faculty and students in educational institutions for the purpose of time management.It involves a very simple procedure to be done by the student counselor to send his/her result to their parents.Moreover, it will be used to the parents to know the performance of their child.This system is useful to students ,faculty and parents to check the overall result. It gives a general depiction about the understudy execution that a staff can oanapt to post and send and an understudy can need to check their outcome.The structure gives login office to the understudies and faculty.The system checks whether the customers have the normal capacity to select and to see moreover purposes of enthusiasm on the courses available.The structure empowers the understudy and workforce to make the educational execution and store it in the database.